Extravagant camp: the queer abjection of Asian America - Eng, Chris A. (Sexual Cultures, 2025)
Illuminates an irreverent queer cultural strategy for grappling with and remaking abject histories of violenceExtravagant Camp takes as its point of critical departure the multiple valences of the word “camp”: the camp, as a geopolitical space and process of concentrating racialized populations, and the campy as a mode of queer expressiveness. Engaging its double meaning, Chris A. Eng explores how camp and encampment have contoured the figure of the Asian American.The book follows campy performances that imaginatively restage the camps that have been central to dominant narratives of Asian American history: Chinese railroad labor, Japanese American incarceration, Vietnam War refugee resettlement, and counterinsurgency camps across US imperial entanglements in the Philippines. Illuminating an eclectic ensemble of performances that grapple with Asian American history—from classical works in the Asian American literary tradition to emerging works of theater and film—Extravagant Camp uncovers Asian American camp as a prevalent yet underappreciated cultural strategy for contesting accounts of Asian American racialization that overly rely on terms of abjection.Theorizing Asian American camp as both a performance strategy and reading practice, Eng examines how artists drag up the maligned racial roles of the coolie, the internee, the refugee, and the diva to make different sense of these histories. Extravagant Camp shows how Asian American camp takes on queerness as a resource to enliven modes of joy, beauty, and pleasure within structures of constraint, revealing the types of power camp retrieves for racialized communities in the face of abjection. Geared toward the extravagant, Asian American camp demands a recognition of queer abjection not as the basis for our undoing, but rather the grounds for a more radical social remaking